The survey of soil-transmitted helminth species abundance in Slovakia with an emphasis on parameters important for their distribution - Ihnacik, Lukáš; Šmigová, Júlia; Šoltys, Jindřich; Bobíková, Diana; Kuzevičová, Žofia; Kuzevič, Štefan; Schusterová, Ingrid; Papajová, Ingrid (Frontiers in Medicine, 2022)
Soil-transmitted helminths (STH) can be easily dispensable in socially disadvantaged groups. The Roma people represent the group most at risk in Slovakia . This study aimed to investigate the occurrence of STH infections in minorities living with animals under low hygienic conditions and on contaminated soil. Subsequently, we identified the risk assessment factors of the STH transmissions based on parasitological results. In our study, STHs were predominantly found among the Roma communities living in unsanitary conditions. The prevalence of Ascaris lumbricoides among the majority was 0.79%, and Trichuris trichiura was 0.05 %. On the contrary, a community-based cross-sectional survey across eastern Slovakia also found a prevalence of 22.28% and 3.47% for A. lumbricoides and T. trichiura among the Roma population. Inhabitants that belong to the Roma minority had a 37.12 infection OR times higher than non-Roma inhabitants. The Roma people living in the countryside have a 2.23-fold higher chance of getting infected with STH than Roma living in the city. Therefore, soil and domestic animals were also examined for the presence of the STH eggs to show the environmental burden. In general, the presence of STH eggs was confirmed in 26.26% of the soil examined samples. The detailed description is as follows: eggs of Toxocara spp., Trichuris spp., eggs from the family Ancylostomatidae, and Toxascaris leonina. Ascaris eggs were detected only in the soil from localities with low hygienic standards. The probability of contracting the STH eggs in segregated settlements was 15.94 times higher compared to urban or rural areas. In addition to humans, dogs can also be a source of STH eggs in the soil. The STH eggs were confirmed in 43.55% of dog droppings. The most interesting finding was that the eggs of the genus Ascaris were up to 7.93% of dog droppings from localities with a low hygienic standard were positive. This study revealed that climatic factors and the WASH conditions influenced the distribution of STHs to variable degrees. In addition, ethnicity and sanitation were crucial factors in the distribution of STH infection in eastern Slovakia.